Impregnação de TiO2 em biochar derivado de resíduo de café para fotodegradação de diclofenaco em soluções aquosas - Lazarotto, Joseane Sarmento (2020)
In this work, a novel composite based on coffee grounds biochar was prepared with immobilized titanium dioxide (TiO2) and used for photodegradation of diclofenac in aqueous solution. Composites with different mass proportions between biochar and TiO2 were prepared by mechanical mixing and subsequent pyrolysis in an inert atmosphere of N2 at 650 ºC. The composites were characterized by X-ray diffraction, scanning electron microscopy, dispersive energy spectroscopy, Fourier-transform infrared spectrometry, specific surface area, pore size and volume. The composite with a 1:1 ratio of biochar-TiO2 (B1T1) showed a degradation efficiency of 90% in just 120 min UV radiation, while the composite with a 2:1 ratio of biochar-TiO2 (B2T1) showed a degradation efficiency of 55 % in 120 min, being higher than bare TiO2, with 40% of degradation efficiency. This fact is associated with a set of intrinsic characteristics obtained during the formation of composites, such as: larger pore size, reduction of the recombination rate of the pair electron (ē)/hole (h+), reduction of the band gap energy and the promotion of reactive species of oxygen due to phenolic groups present on the surface of the biochar. The dominant reactive species involved during the photocatalytic degradation of diclofenac were h+ and •OH. Diclofenac's degradation pathways were determined based on the identification of the intermediates and the analysis of non-purgable organic carbon (NPOC). The novel biochar-TiO2 composite prepared in this work showed high physical-chemical stability and efficiency in five consecutive reuse cycles, proving to be a highly promising photocatalyst to degrade diclofenac in water, in addition to being a sustainable alternative, since it reuses and enhances a waste for the production of biochar.